The Influence of Environmental, Social, and Governance (ESG) Disclosure on Firm Value: An Asymmetric Information Perspective in Indonesian Listed Companies - Putri Angir; Weli Weli (Binus Business Review, 2024)
The research explored how Environmental, Social, and Governance (ESG) disclosure impacted company value, with information asymmetry as the mediator. Data collection involved content analysis of sustainability and annual reports, supplemented by market data, including quarterly stock prices collected immediately after the publication of the sustainability report. The measurement for ESG disclosure used the index scoring method with disclosure indicators based on technical guidelines from SEOJK No. 16 of 2021. Meanwhile, measuring information asymmetry applied the bid-ask spread formula, and company value employed the approximate Tobin's Q formula. Then, market data utilized quarterly stock prices taken in the period immediately after the sustainability report was published to observe market reactions reflected in stock price movements. The population consisted of public companies listed on the Indonesian Stock Exchange from 2019 to 2021, with purposive sampling by selecting only companies that provided information relevant to ESG indicators. Data collection resulted in 286 analysis units from 109 companies. Using SPSS 27.0 and the Hayes Macro process for path analysis, the findings indicate that ESG disclosure has no impact on information asymmetry. Similarly, information asymmetry does not affect firm value or mediate the relationship between ESG disclosure and firm value. However, it should be noted that ESG disclosure has a negative impact on company value. The novelty of the research lies in the use of instruments to assess the quality of ESG disclosure and the utilization of information asymmetry as a mediator between ESG disclosure and company value.